The management of lions (Panthera Leo) in small, fenced wildlife reserves - McEvoy, Orla (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Reintroduced lion (Panthera leo) populations pose several ecological and management challenges in small (< 1,000 km2), fenced wildlife reserves. Changes in the natural socialecological conditions of reintroduced lion populations may lead to rapid population growth and a breakdown of natural predator-prey relationships. Reduced competition with other lions also likely reduces the potential for reintroduced lions to naturally form groups. My study used a combination of questionnaire surveys with tourists, existing lion demographic data from 16 wildlife reserves across South Africa and a controlled lion social experiment to address these ecological and management issues. Tourism was the primary reason for lion reintroductions. Tourists scored lions highly in terms of preference for viewing on safari, in particular, lions in larger, natural groups and adult males. Viewing lions also enhanced a tourists' overall safari experience. The breakdown of natural social behaviour may likely therefore reduce tourist satisfaction related to lions. The number of resident prides and male coalitions in a reserve affected lion vital rates. Lion population growth rate was highest in reserves that contained a single resident pride, and the presence of unknown adult males significantly reduced cub survival and lioness birth intervals. The ratio of male cubs born also increased in reserves with a higher density of unknown adult males. Fertility control measures (deslorelin implants and unilateral hysterectomy) were effective at limiting lion population growth. Deslorelin treatment increased the age of first reproduction or the birth interval and decreased the subsequent litter size of treated lionesses to closer reflect natural vital rates in larger (> 10, 000 km2) systems. However, there was variability in infertility response between lionesses including adverse reactions in a small proportion of treated individuals. The number of resident prides and male coalitions in a reserve affected lion social behaviour. Lionesses formed larger groups in reserves with a higher density of unknown adult female neighbours, likely driven by territory defence. Lion prides with resident cubs were generally more fragmented, likely in response to reduced competition from unknown adult males. However, in areas with a high density of unknown adult female neighbours, prides with cubs formed larger groups likely in response to heightened territory defence. Therefore, with smaller foraging group sizes, predation rate was increased in reserves with reduced competition from unknown lions. My study supports a metapopulation approach for the management of lions in small, fenced reserves, and the standardisation of lion management procedures and database management. Endorsed by the Biodiversity Management Plan for lions in South Africa, this will enhance the long-term conservation potential of isolated populations.
Keywords: Lion -- Behavior -- South Africa; Spatial behavior in animals -- South Africa; Animal populations -- South Africa; Game reserves -- South Africa -- Management